Morphology and microstructure of chromite crystals in chromitites from the Merensky Reef (Bushveld Complex, South Africa) - Vukmanovic, Z.; Barnes, S.; Reddy, Steven; Godel, B.; Fiorentini, M. (Springer, 2013)
The Merensky Reef of the Bushveld Complex consists of two chromitite layers separated by coarse-grained melanorite. Microstructural analysis of the chromitite layers using electron backscatter diffraction analysis (EBSD), high-resolution X-ray microtomography and crystal size distribution analyses distinguished two populations of chromite crystals: fine-grained idiomorphic and large silicate inclusion-bearing crystals. The lower chromitite layer contains both populations, whereas the upper contains only fine idiomorphic grains. Most of the inclusion-bearing chromites have characteristic amoeboidal shapes that have been previously explained as products of sintering of pre-existing smaller idiomorphic crystals. Two possible mechanisms have been proposed for sintering of chromite crystals: (1) amalgamation of a cluster of grains with the same original crystallographic orientation; and (2) sintering of randomly orientated crystals followed by annealing into a single grain. The EBSD data show no evidence for clusters of similarly oriented grains among the idiomorphic population, nor for earlier presence of idiomorphic subgrains spatially related to inclusions, and therefore are evidence against both of the proposed sintering mechanisms. Electron backscatter diffraction analysis maps show deformation-related misorientations and curved subgrain boundaries within the large, amoeboidal crystals, and absence of such features in the fine-grained population. Microstructures observed in the lower chromitite layer are interpreted as the result of deformation during compaction of the orthocumulate layers, and constitute evidence for the formation of the amoeboid morphologies at an early stage of consolidation.An alternative model is proposed whereby silicate inclusions are incorporated during maturation and recrystallisation of initially dendritic chromite crystals, formed as a result of supercooling during emplacement of the lower chromite layer against cooler anorthosite during the magma influx that formed the Merensky Reef. The upper chromite layer formed from a subsequent magma influx, and hence lacked a mechanism to form dendritic chromite. This accounts for the difference between the two layers.